If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -4n = 1 + -5n Solving -4 + -4n = 1 + -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. -4 + -4n + 5n = 1 + -5n + 5n Combine like terms: -4n + 5n = 1n -4 + 1n = 1 + -5n + 5n Combine like terms: -5n + 5n = 0 -4 + 1n = 1 + 0 -4 + 1n = 1 Add '4' to each side of the equation. -4 + 4 + 1n = 1 + 4 Combine like terms: -4 + 4 = 0 0 + 1n = 1 + 4 1n = 1 + 4 Combine like terms: 1 + 4 = 5 1n = 5 Divide each side by '1'. n = 5 Simplifying n = 5
| x+6*x-9=30 | | 3[x-2]=27 | | 2y=2y+44 | | 40+4x=12(x+20) | | 5-8m=14-5m | | 1.7-x=1.2 | | g/-4=-4.21 | | x+6x*-9=30 | | 5x^4-40x^2=0 | | M+23=94 | | 5k+4=3k-2k | | 3.1=x-1.5 | | 4/6r=5 | | x+6a*-9=30 | | 3n-n=4+n | | x=10*log(100) | | x-0.6=1.1 | | g-4= -4.21 | | 4z+5=6z-3z | | r/2=-18 | | -28=-2(w+7) | | x=1000*log | | -12+8n=-2n+4n | | u=2u-64 | | 12n+20=(n+5)*7 | | -4k=-19.6 | | c=40+55h | | 14x-5=12x-5 | | (n-5)*6=3n-6 | | 2.6+10m=8.29 | | -2(x+2)=4-(5x-7) | | 4x+6=2+3x-1 |